1942
DOI: 10.1084/jem.75.1.77
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sulfapyridine Upon the Development of Immunity to Pneumococcus in Rabbits

Abstract: 1. Sulfapyridine, administered to rabbits during the period of developing immunity after a single intravenous injection of heat-killed Pneumococcus Type I, exerted no influence upon the immune response. 2. Active immunity as indicated by increased resistance to homologous intradermal infection was present 48 hours after the immunizing injection and 2 days before circulating type specific antibodies were detectable. 3. Of the serological techniques employed for the detection of cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1942
1942
1962
1962

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Indeed, as little as 6 X 10 ~ plaque-forming phage (approximately 10 -s #g. protein) sufficed to stimulate detectable antibody formation in 3 of 10 animals. There are several reports in the literature of similarly early antibody formation following a first administration of antigen (19)(20)(21), however, the specificity (immune nature) of the early response and/or the absence of previous antigenic stimulation was usually not satisfactorily established. Of particular interest to our studies is a statement of Jerne (22) that a second dose of T~ bacteriophage is more rapidly removed from the circulation of rabbits if a first injection had been given at least 48 hours previously.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as little as 6 X 10 ~ plaque-forming phage (approximately 10 -s #g. protein) sufficed to stimulate detectable antibody formation in 3 of 10 animals. There are several reports in the literature of similarly early antibody formation following a first administration of antigen (19)(20)(21), however, the specificity (immune nature) of the early response and/or the absence of previous antigenic stimulation was usually not satisfactorily established. Of particular interest to our studies is a statement of Jerne (22) that a second dose of T~ bacteriophage is more rapidly removed from the circulation of rabbits if a first injection had been given at least 48 hours previously.…”
Section: Discussionmentioning
confidence: 99%
“…(Received for publication August 3, 1942) As a result of qualitative and relative tests (1,2), it is generally agreed that rapid termination of lobar pneumonia in man by means of drugs of the sulfanilamide group does not prevent development of the immune response long recognized as characteristic of spontaneous recovery from the disease and evidenced by the formation of type-specific anticarbohydrate. Nothing is known, however, of the magnitude of this immune response in absolute terms, beyond a single report of 0.15 mgm.…”
mentioning
confidence: 99%
“…The early development of circulating antibodies and active 'resistance was not influenced by the administration of sulfonamide (11)(12)(13).…”
Section: Discussionmentioning
confidence: 93%
“…of pneumococcal infections in both man (1-8) and animals (9)(10)(11)(12)(13) have shown that the development of specific antibodies is not affected by early therapy with sulfonamide drugs. In contrast, early penicillin therapy of rabbits and mice (14) and of rats (15) Twenty-nine patients received initial penicillin doses of from 20,000 to 50,000 units intramuscularly; 12 patients were given 100,000 units, and three patients 300,000 units.…”
mentioning
confidence: 99%
See 1 more Smart Citation